Nickel Selenide Quantum Dot Applications in Electrocatalysis and Sensors. Issue 12 (14th October 2020) - Tito, Ginny S.; Abolanle, Adekunle S.; Kuvarega, Alex T.; Idris, Azeez O.; Mamba, Bhekie B.; Feleni, Usisipho
Abstract: Quantum dots (QDs) are semiconducting materials with diameters ranging from 2–10 nm. Amongst these QDs, nickel selenide quantum dot (NiSeQD) materials have gained much interest from researchers over the past few years due to their outstanding properties. These include excellent catalytic activity, good electrical conductivity for charge transfer, and excellent thermodynamic stability. NiSeQD material is relatively cheap, less toxic, and can be synthesised easily. Due to the fascinating and remarkable properties of NiSeQD, the material has been applied in various electrochemical fields, including hydrogen evolution reaction (HER), oxygen evolution reaction (OER), and solar cells. This review focuses on the application of NiSeQD and its composites in the various analytical fields in the search for alternative renewable sources of energy. Interestingly, NiSeQD material can be modified with different materials to improve its sensitivity, reactivity, and limit of detection. The effects of modification with other materials such as iron (Fe), cobalt (Co), and graphene (GN) are mentioned. Additionally, the application of NiSeQD in glucose sensing is discussed briefly. In these aforementioned applications, NiSeQD has shown excellent electrocatalytic capability with satisfactory detection limits and good conductivity. Thus, further exploration of it to other fields is essential. This review highlights the importance of NiSeQD in water purification, and no report has been documented in the literature on its application in water purification. Some gaps are still open for the use of NiSeQD material as an electroactive platform for sensing devices in water treatment. Abstract :